1993
DOI: 10.1002/1097-0142(19930615)71:12<4091::aid-cncr2820711247>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Childhood intracranial meningiomas after high-dose irradiation

Abstract: Background. Irradiation, either alone or in association with other factors, is thought to play a role in the causation of intracranial meningioma. Methods. The authors report two 15‐year‐old patients with convexity meningiomas as a result of high‐dose irradiation received at a young age and review the English language literature reports of 13 pediatric patients with meningiomas after high‐dose irradiation. The clinical characteristics of the 15 patients are presented. Results. There were nine girls and six boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 24 publications
2
40
0
1
Order By: Relevance
“…In their survey of reported cases of RIM in patients exposed to high-dose radiation, Strojan et al 78 observed average latency of 18.7 years and also noted shorter latency in patients in whom radiation treatments were administered at younger ages. Ghim et al 17 found a mean latency of only 10.8 years (range 5-15.5) in a study of 13 pediatric high-dose RIM patients with mean age at diagnosis 13 years (range 6-18). These patients had been treated for brain tumors at an average age of 2.5 years.…”
Section: Radiation-induced Meningiomamentioning
confidence: 98%
See 4 more Smart Citations
“…In their survey of reported cases of RIM in patients exposed to high-dose radiation, Strojan et al 78 observed average latency of 18.7 years and also noted shorter latency in patients in whom radiation treatments were administered at younger ages. Ghim et al 17 found a mean latency of only 10.8 years (range 5-15.5) in a study of 13 pediatric high-dose RIM patients with mean age at diagnosis 13 years (range 6-18). These patients had been treated for brain tumors at an average age of 2.5 years.…”
Section: Radiation-induced Meningiomamentioning
confidence: 98%
“…3,28 Harrison et al 24 grouped RIMs into 3 categories: those due to high-dose (Ͼ 20 Gy), intermediate-dose (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and low-dose (Ͻ 10 Gy) radiation. Other authors define doses Ͼ 10 Gy as high.…”
Section: Radiation-induced Meningiomamentioning
confidence: 99%
See 3 more Smart Citations